Model-based Method for the Accuracy Analysis of Hardware-in-the-Loop Test Rigs for Mechatronic Vehicle Axles. (2016) - Olma, S.; Traphöner, P.; Kohlstedt, A.; Jäker, K.-P.; Trächtler, A.
Abstract: This paper presents a model-based method to analyze the accuracy of Hardware-in-the-Loop (HiL) test rigs for mechatronic vehicle axles. In the first part of the method, the general HiL system structure is investigated and appropriate assessment criteria are defined. Subsequently, dynamic models of all subsystems are developed. The analysis itself is performed in two steps. Firstly, the individual subsystems are investigated. Secondly, the entire closed-loop system is analyzed according to the emulation fidelity to a reference system. The developed method is validated by its application to a HiL test rig for mechatronic vehicle axles.